Geometrical Distribution of Cryptococcus neoformans Mediates Flower-Like Biofilm Development - Lopes, William; Vainstein, Mendeli H.; De Sousa Araujo, Glauber R.; Frases, Susana; Staats, Charley C.; de Almeida, Rita M. C.; Schrank, Augusto; Kmetzsch, Lívia; Vainstein, Marilene H. (Frontiers in Microbiology, 2017)
Microbial biofilms are highly structured and dynamic communities, in which phenotypic diversification allows microorganisms to adapt to different environments under distinct conditions. The environmentally ubiquitous pathogen Cryptococcus neoformans colonizes many niches of the human body and implanted medical devices in the form of biofilms, an important virulence factor. A new approach was used to characterize the underlying geometrical distribution of C. neoformans cells during the adhesion stage of biofilm formation. Geometrical aspects of adhered cells were calculated from the Delaunay triangulation and Voronoi diagram obtained from scanning electron microscopy images (SEM). A correlation between increased biofilm formation and higher ordering of the underlying cell distribution was found. Mature biofilm aggregates were analyzed by applying an adapted protocol developed for ultrastructure visualization of cryptococcal cells by SEM. Flower-like clusters consisting of cells embedded in a dense layer of extracellular matrix were observed as well as distinct levels of spatial organization: adhered cells, clusters of cells and community of clusters. The results add insights into yeast motility during the dispersion stage of biofilm formation. This study highlights the importance of cellular organization for biofilm growth and presents a novel application of the geometrical method of analysis.